Enhancing graph interpretation skills of Grade 9 students in learning microeconomics through I2 strategy - Calingacion, Jojenn P.; Dacera, Alyssa Lira M.; Castro, Melissa G.; Lubay, Joshua C.; Bug-os, Rona Flor Fatima C.; Bansale, Jay C. (Indonesian Journal of Education and Pedagogy, 2025)
This action research aimed to enhance the graph interpretation skills of 35 Grade 9 Apitong students of Baybay National High School in learning microeconomics through the I2 strategy. Utilizing a mixed-methods research design, the study incorporated pre-and post-assessments to evaluate students' graph interpretation skills. Quantitative data were analyzed using the Wilcoxon signed-rank test to assess significant differences in performance, while thematic analysis was employed to gain insights into students' experiences with the I2 strategy. The findings revealed a significant improvement in students’ graph interpretation skills after the implementation of the strategy. Thematic analysis results highlighted mastery of graphing skills, and enhanced learning experience and skill master in interpreting graphs. Notably, the I2 strategy proved instrumental in enhancing the ability of Grade 9 students, who initially had a poor understanding and interpretation of graphs in learning microeconomic concepts.